2014
DOI: 10.3892/mmr.2014.2162
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA targeting ILK inhibits EMT in human peritoneal mesothelial cells through phosphorylation of GSK-3β

Abstract: Emerging evidence has suggested that human peritoneal mesothelial cells (HPMCs) undergo epithelial‑mesenchymal transition (EMT) in peritoneal fibrosis. The molecular mechanisms underlying peritoneal fibrosis and the key molecules involved are not yet fully elucidated. In order to enhance the understanding of peritoneal fibrosis, the present study investigated the roles of integrin‑linked kinase (ILK) and glycogen synthase kinase 3β (GSK‑3β) in high glucose‑induced phenotypic alterations of HPMCs. It was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…30 Additionally, knockout of ILK decreased the invasion and metastasis abilities of cells through inhibiting the EMT process. 31 , 32 Considering the crucial roles of EMT in modulating cell migration and invasion, ILK may be a promising treatment target for various diseases. Tang et al discovered that emodin inhibited the expression of ILK through the crosstalk of AMPKα and ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Additionally, knockout of ILK decreased the invasion and metastasis abilities of cells through inhibiting the EMT process. 31 , 32 Considering the crucial roles of EMT in modulating cell migration and invasion, ILK may be a promising treatment target for various diseases. Tang et al discovered that emodin inhibited the expression of ILK through the crosstalk of AMPKα and ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Knockout of the ILK gene inhibited the EMT program in human peritoneal mesothelial cells through phosphorylation of GSK-3β. 32 Moreover, inhibition of GSK-3β is crucial for EGF-induced EMT in human prostate and lung cancer. 38 Previous studies indicated that GSK-3β played a crucial role in controlling the expression of β-catenin in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Akt phosphorylates GSK-3β at Ser 9, leading to inactivation of its kinase activity, and ILK can phosphorylate GSK-3β at Ser 9 in Akt-independent way [23]. Luo et al [24] demonstrated that ILK knockdown inhibits EMT through inhibition of GSK-3β phosphorylation at Ser 9. On the other hand, actions which promote cell death, such as growth factor removal, stimulate kinase activity by increasign phosphorylation within the catalytic domain at Tyr 216.…”
Section: Discussionmentioning
confidence: 99%
“…ILK is widely expressed in several types of human cancers including glioma and has been positively correlated with tumor growth and closely related to tumor apoptosis, proliferation, invasion and migration (13,14). ILK is a ubiquitously expressed serine/threonine protein kinase that binds directly to the cytoplasmic domains of β1 and β3 integrins and has been shown to have clinical/prognostic and functional significance in various human cancers.…”
Section: Discussionmentioning
confidence: 99%